The Scholems : a story of the German-Jewish bourgeoisie from emancipation to destruction - Geller, Jay Howard (University Press Pilot Project, 2019)
"A collective biography of the family of the Jewish scholar Gershom Scholem and a social history of the Jewish middle class in Germany from the era of emancipation through the Holocaust"--